E-books in libraries [ - Tedd, Lucy A. (Program: electronic library and information systems, 2007)
In May 2007 a one-day seminar on "Putting content in context" at University College London stated in its introductory information, "E-books have finally become accepted in many organizations and licensed e-content is proliferating through library catalogues and web portals." The development of electronic versions of printed books (or e-books) can be seen as part of the whole e-publishing phenomenon that began in the 1960s. E-books are fast becoming a central part of the modern library, and thus the practical issues surrounding their use must be considered. This e-book brings together a number.